"Transformative" Reflection: Re-defining Reflection Towards a Shared Destination - Balzotti, Jon; Rowan, Jamin; Duerden, Mat (Experiential Learning and Teaching in Higher Education, 2025)
This essay reevaluates the role of reflection in experiential learning programs, contrasting traditional solitary reflection methods with contemporary approaches that integrate collaboration and multimodal expression. These new approaches highlight a shift toward collaborative and interactive models, reflecting the influence of new technologies and pedagogical strategies. Through a case study of the “My London Story” study abroad program, which implemented a transformative reflection model guided by transformative learning objectives (TLOs), this paper explores how reflective practices can foster significant, shared learning outcomes. The program, spanning January to April 2023, involved 45 students who engaged in various reflective activities, including weekly prompts, group discussions, and a final multimedia project. The use of TLOs—focusing on curiosity and creativity—encouraged students to reflect not only on their experiences but also on their evolving identities and capabilities. The essay concludes that integrating new forms of reflective writing and digital media into experiential learning can profoundly enrich students’ self-awareness and prepare them for future challenges, emphasizing the need for intentional, mentored reflection to achieve transformative learning outcomes.